SARS-CoV-2 spike protein induces salivary gland dysfunction and immune infiltration in C57BL/6 mice - Felix, Fernanda Aragão; Jiang, Yuqiao; Zhou, Jing; Li, Dongfang; Zhou, Victoria; de Sousa, Sílvia Ferreira; Byrd, Kevin Matthew; Yu, Qing (Frontiers in Immunology, 2025)
Salivary gland dysfunction and inflammation are common following SARS-CoV-2 infection. This study aimed to investigate the effects of SARS-CoV-2 spike and envelope proteins on glandular function in healthy C57BL/6 mice through direct intra-glandular injection into the submandibular glands. Local administration of spike protein significantly reduced salivary secretion, while the envelope protein had no measurable impact. Histological analysis revealed the presence of leukocyte foci in two-thirds of spike protein-treated mice, while none were detected in the vehicle- or envelope protein-treated groups. Furthermore, spike protein treatment led to a significant increase in total immune cells and B cells, and an expansion of the CD44high CD62Llow effector/effector memory subsets within CD4 T cells and B cells in the submandibular glands. Notably, serum antinuclear antibodies developed in one-third of spike-treated mice, consistent with the reported salivary gland pathology in COVID-19 patients that resemble autoimmune Sjögren’s disease. Moreover, spike protein treatment increased phospho-STAT3 levels and induced transcriptomic changes indicating impaired acinar compartment, heightened adaptive immune responses, and altered tissue remodeling activity. These findings show that SARS-CoV-2 spike protein alone is sufficient to initiate significant salivary gland pathology in the absence of intact virus or ACE2 interaction, providing evidence for a novel mechanism by which SARS-CoV-2 induces salivary gland dysfunction and pathology with autoimmune features.